(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
Surface water from the Rio Grande River is one of the primary water sources for southern New Mexico and Far West Texas in the United States (U.S.) and northern Chihuahua in Mexico. The river supplies several users, including agriculture, municipalities, industry, and wildlife. Surface water from precipitation, lakes, ponds, and swamps plays a significant role in the region’s water supplies. However, climate change and the fast growth of the major metropolitan areas of El Paso, Ciudad Juárez, and Las Cruces have resulted in changes in land-use practices and increased water demand in response to growing competition between urban water needs and other uses. This study applies the Modified Normalized Difference Water Index (MNDWI) to visualize, monitor, and identify changes in surface water bodies in the Middle Rio Grande River Basin for a 26-year 1994-2020 study period. The area spans from San Antonio, New Mexico, to Presidio, Texas, and to Ojinaga, Chihuahua, including the cities of El Paso, Texas, Ciudad Juárez, Chihuahua, and Las Cruces, New Mexico, all metropolitan areas on the U.S.-Mexico border. Results show that surface waterbodies have experienced an overall decrease in surface area during the last twenty-six years by more than 66 percent. This decrease is especially evident for the Elephant Butte and Caballo reservoirs, which decreased by about 83 percent and 72 percent, respectively. In 2020, surface waterbodies increased by approximately 31.9 % compared to 2018 storage and reduced the surface water area decrease to 46.9 percent. Geographic information systems (GIS) and remote sensing (RS) proved useful tools for analyzing surface water change over time and monitoring mesoscale regions experiencing climate change, rapid urban growth, and water scarcity.